Language Style In Five Dorothea Rosa Herliany’s Poems in 2020/2021 - Masyudi Masyudi (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study is aimed to find out the language styles in five Dorothea Rosa Herliany’s poems in 2020/2021. Saint Rosa 1, Saint Rosa 2, Visitors to History, Children’s Games and Melancholy Memo. The source of data in this study is a book entitled Santa Rosa Saint Rosa Dorothea Rosa Herliany [Poems] written by Dorothea Rosa Herliany, edited and translated by Harry Aveling, published by Indonesian Tera in 2005. The method of data collection in this study is documentary. The data gathered through documentary method were analyzed by using descriptive method. It was found out that Saint Rosa 1, Saint Rosa 2, Visitors to History, Children’s Games and Melancholy Memo contain several languages styles in terms of hyperbola, litotes, irony, antithesis, personification, simile, metaphor, allegory, ellipsis, repetition, parallelism and chiasmus.